The Transmission Characteristic of Metal–Dielectric–Metal Slot Waveguide-Based Nanodisk Cavity With Gain Medium - Yan Liu (IEEE Photonics Journal, 2015)
We theoretically investigate the propagation of surface plasmon polaritons (SPPs) for the metal-dielectric-metal slot waveguide coupled to a disk cavity filled with gain material. The transmission and reflection characteristics of the resonant structure are numerically analyzed based on coupled-mode theory. The influence of structure parameters on the spectra of transmission is investigated using a finite-element method. In addition, the incorporation of gain medium can compensate for the loss from metal and, thus, enable the loss-negligible SPP propagation in near-infrared wavelengths, which makes a novel approach of optical switches and lasers based on SPPs possible in the planar optoelectronic compact integration.